2009
DOI: 10.1519/jsc.0b013e31818eaef3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compression Stockings on Running Performance in Men Runners

Abstract: The purpose of this study was to determine the effect of below-knee compression stockings on running performance in men runners. Using a within-group study design, 21 moderately trained athletes (39.3 +/- 10.9 years) without lower-leg abnormities were randomly assigned to perform a stepwise treadmill test up to a voluntary maximum with and without below-knee compressive stockings. The second treadmill test was completed within 10 days of recovery. Maximum running performance was determined by time under load (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
110
1
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(132 citation statements)
references
References 17 publications
10
110
1
11
Order By: Relevance
“…• No differences in the physiological variables of heart rate, oxygen consumption, rating of perceived exertion, or lactate levels were found with the use of GCS. [3][4][5][6] • Two studies, 1 with 2 separate experiments, showed no difference in running performance while wearing GCS. 3,6 • Two studies showed that GCS were effective in improving performance as measured by either maximal work 5 or running performance.…”
Section: Summary Of Search "Best Evidence Appraised"mentioning
confidence: 99%
See 3 more Smart Citations
“…• No differences in the physiological variables of heart rate, oxygen consumption, rating of perceived exertion, or lactate levels were found with the use of GCS. [3][4][5][6] • Two studies, 1 with 2 separate experiments, showed no difference in running performance while wearing GCS. 3,6 • Two studies showed that GCS were effective in improving performance as measured by either maximal work 5 or running performance.…”
Section: Summary Of Search "Best Evidence Appraised"mentioning
confidence: 99%
“…3,6 • Two studies showed that GCS were effective in improving performance as measured by either maximal work 5 or running performance. 4 • One study showed that GCS improved maximum running speed. 4 • One study showed lower ratings of perceived muscle soreness 24 hours after exercise with the use of GCS.…”
Section: Summary Of Search "Best Evidence Appraised"mentioning
confidence: 99%
See 2 more Smart Citations
“…Leistungssteigernde Effekte im Sinne von einer erhöhten Laufgeschwindigkeit bei der aeroben und anaeroben Schwelle, bei einem Stufentest auf dem Laufband, observierte Kemmler et al (2009) [3]. Ähnliche Ergebnisse präsentierte Bringard et al (2006) bezogen auf einen signifikant niederen aerobe Energieaufwand bei elastischen Kompressionshosen im Vergleich zu normalen Trainingshosen [8].…”
unclassified